2006
DOI: 10.1016/j.nbd.2005.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Age-related evolution of amyloid burden, iron load, and MR relaxation times in a transgenic mouse model of Alzheimer's disease

Abstract: T1 and T2 magnetic resonance relaxation times have the potential to provide biomarkers of amyloid-beta deposition that could be helpful to the development of new therapies for Alzheimer's disease. Here, we measured T1 and T2 times as well as plaques and iron loads in APP/PS1 mice, which model brain amyloidosis, and control PS1 mice. Iron was mostly associated with amyloid deposits in APP/PS1 animals, while it was diffuse in the PS1 mice. T1 was negatively correlated with age in most structures in APP/PS1 anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
76
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 45 publications
13
76
2
Order By: Relevance
“…The PIB data show that in AD, Aβ deposition is also observed predominantly in late-myelinating regions [35][36][37] (Figure 1A, C). We hypothesized that myelin breakdown in vulnerable late-myelinating regions ( Figure 1B, D) releases oligodendrocyte-and myelin-associated iron [19,21,28,38,39], thus promoting Aβ oligomerization, its associated toxicity, and deposition of oligomerized Aβ and iron in neuritic plaques [7,28,[40][41][42][43] (Figure 1A, C). This hypothesis has been supported in transgenic mouse models that demonstrated increased vulnerability of oligodendrocytes to toxicity [44], agerelated white matter volume reductions [45], and age-related iron deposition in amyloid plaques [42].…”
Section: Methods Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The PIB data show that in AD, Aβ deposition is also observed predominantly in late-myelinating regions [35][36][37] (Figure 1A, C). We hypothesized that myelin breakdown in vulnerable late-myelinating regions ( Figure 1B, D) releases oligodendrocyte-and myelin-associated iron [19,21,28,38,39], thus promoting Aβ oligomerization, its associated toxicity, and deposition of oligomerized Aβ and iron in neuritic plaques [7,28,[40][41][42][43] (Figure 1A, C). This hypothesis has been supported in transgenic mouse models that demonstrated increased vulnerability of oligodendrocytes to toxicity [44], agerelated white matter volume reductions [45], and age-related iron deposition in amyloid plaques [42].…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…We hypothesized that myelin breakdown in vulnerable late-myelinating regions ( Figure 1B, D) releases oligodendrocyte-and myelin-associated iron [19,21,28,38,39], thus promoting Aβ oligomerization, its associated toxicity, and deposition of oligomerized Aβ and iron in neuritic plaques [7,28,[40][41][42][43] (Figure 1A, C). This hypothesis has been supported in transgenic mouse models that demonstrated increased vulnerability of oligodendrocytes to toxicity [44], agerelated white matter volume reductions [45], and age-related iron deposition in amyloid plaques [42]. Human studies have likewise confirmed age-related myelin breakdown that is exacerbated in healthy APOE e4 carriers and AD subjects [7,43] and age-related increases in brain iron [21] that are exacerbated in AD subjects [28].…”
Section: Methods Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations